ANALISIS RASIO LIKUIDITAS DAN RASIO RENTABILITAS UNTUK MENILAI KINERJA KEUANGAN PADA PT. MUSTIKA RATU, TBK - Gulo, Ani Putri (Universitas Nias Raya, 2024)
This research aims to find out how the financial performance of PT. Mustika Ratu, Tbk during 2012-2021 based on analysis of liquidity ratios and profitability ratios. The type of research used in this research is descriptive qualitative research. The results of this research indicate that the level of health of PT's financial performance. Mustika Ratu is in the bad category. Based on the liquidity ratio, the level of financial health at PT. Mustika Ratu Tbk from 2012-2021 is classified as not good. From the profitability ratio aspect, the level of financial health in 2012-2021 is classified as poor because it does not meet the average industry standard. Thus it can be said that from the aspect of liquidity ratios and profitability ratios of PT. Mustika Ratu has poor financial performance in operating and competing in the business world in the cosmetics industry. The suggestion in this research is that in order for the company's financial performance to be good, the company should carry out ratio analysis to find out more deeply the condition or state of the company's financial report performance.